Modelling emplacement of magmatism on the Iberia microplate during the Late Cretaceous - Araújo, Bruno Miguel Duarte de (2023)
Tese de mestrado, Geologia Estrutural, 2023, Universidade de Lisboa, Faculdade de Ciências